Age matters in the prevalence and clinical significance of ultra‐high‐risk for psychosis symptoms and criteria in the general population: Findings from the BEAR and BEARS‐kid studies. Issue 2 (June 2015) - Schimmelmann, Benno G.; Michel, Chantal; Martz-Irngartinger, Alexandra; Linder, Caroline; Schultze-Lutter, Frauke
<x xml:space="preserve">Abstract</x> Early detection of psychosis is an important topic in psychiatry. Yet, there is limited information on the prevalence and clinical significance of high‐risk symptoms in children and adolescents as compared to adults. We examined ultra‐high‐risk (UHR) symptoms and criteria in a sample of individuals aged 8‐40 years from the general population of Canton Bern, Switzerland, enrolled from June 2011 to May 2014. The current presence of attenuated psychotic symptoms (APS) and brief intermittent psychotic symptoms (BLIPS) and the fulfillment of onset/worsening and frequency requirements for these symptoms in UHR criteria were assessed using the Structured Interview for Psychosis Risk Syndromes. Additionally, perceptive and non‐perceptive APS were differentiated. Psychosocial functioning and current non‐psychotic DSM‐IV axis I disorders were also surveyed. Well‐trained psychologists performed assessments. Altogether, 9.9% of subjects reported APS and none BLIPS, and 1.3% met all the UHR requirements for APS. APS were related to more current axis I disorders and impaired psychosocial functioning, indicating some clinical significance. A strong age effect was detected around age 16: compared to older individuals, 8‐15‐year olds reported more perceptive APS, that is, unusual perceptual experiences and attenuated hallucinations. Perceptive APS were generally less related to functional impairment, regardless of age. Conversely, non‐perceptive APS were related to low functioning, although this relationship was weaker in those below age 16. Future studies should address the differential effects of perceptive and non‐perceptive APS, and their interaction with age, also in terms of conversion to psychosis.